Observing political and societal changes in Finnish parliamentary speech data, 1980–2010, with topic modelling - Ristilä Anna; Elo Kimmo (Routledge, 2025)
Parliamentary speech reflects many events, changes and developments in society, as well as shaping them by influencing legislation and public interest. Knowing what topics have been dominant in parliamentary discussions can reveal what has been considered important at the time the speech was given. This knowledge can be achieved computationally with topic modelling, which can identify latent topics in large numbers of texts. Currently, the method is still underused in parliamentary studies and has only previously been used once with Finnish parliamentary speeches. This article aims to create and validate a topic model offering a robust overview of Finnish parliamentary speeches from 1980 to 2010, and to demonstrate the validity of the model by examining peaks in topic occurrences and comparing them to the historical and societal context at the times. The topics ‘energy’, ‘employment’ and ‘democracy’ were selected for closer inspection.